Quinolinacridine-5, 9-dione MR-TADF red light emitting material as well as preparation method and application thereof

By designing the MR-TADF red light emitting material with quinoline-5,9-dione as the central core, the resonance effect suppresses the relaxation and vibration coupling of the excited state of the molecule, the luminous color of the existing red light TADF material is solved by using the resonance effect to suppress the relaxation and vibration coupling of the excited state of the molecule. The problem of low purity achieves narrow spectrum and efficient red light emission, which is suitable for red OLEDs devices.

CN119462691AActive Publication Date: 2025-02-18CHANGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411778215.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The luminous purity of existing red light TADF materials is not high, resulting in the limitation of the color gamut and resolution of the device. The development of high-efficiency narrow spectrum red light MR-TADF materials has problems such as high material R&D cost, high synthesis difficulty and low yield.

Method used

A class of MR-TADF red luminescent materials with quinoline-5,9-dione as the central core and fused oxygen-bridged triphenylamine were designed, and produced by electron-deficient nitrogen/carbonyl and electron-rich oxygen/nitrogen-rich Resonance effect inhibits structural relaxation and vibration coupling of molecular excited states to achieve narrow spectrum luminescence.

Benefits of technology

A red light emitting material with half-maximum width narrow (<70nm) and high luminous efficiency is achieved. It is suitable for red OLEDs devices, improving the color purity and display performance of the device, and reducing the recombination energy and synthesis difficulty of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172070220000031
    Figure BDA0005172070220000031
  • Figure BDA0005172070220000041
    Figure BDA0005172070220000041
  • Figure BDA0005172070220000042
    Figure BDA0005172070220000042
Patent Text Reader

Abstract

The invention discloses a quinolinacridine-5, 9-dione MR-TADF red light emitting material as well as a preparation method and application thereof, and belongs to the technical field of organic photoelectric materials. Molecules of the material generate a resonance effect through electron-deficient nitrogen / carbonyl and electron-rich oxygen / nitrogen, minimization of bonding / anti-bonding of a leading edge molecular orbital is promoted, in addition, a rigid conjugated skeleton inhibits structural relaxation of a molecular excited state and vibration coupling between the excited state and a ground state, and therefore, the stability of the material is improved. The red light emitting material with narrow half-peak width (less than 70nm) and high luminous efficiency is obtained; tert-butyl is introduced to the periphery of the molecule, so that the recombination energy of the molecule can be reduced; by grafting different substituent units, the accumulation and film-forming properties of molecules can be regulated and controlled. The maximum emission peak of the obtained doped red light electroluminescent device is 601 nm, the half-peak width is 68 nm, the corresponding maximum external quantum efficiency is 9.38%, and the doped red light electroluminescent device has wide application in the fields of organic electroluminescent displays, biological imaging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic photoelectric materials, and specifically relates to a type of quinoline acridine-5,9-dione MR-TADF red light emitting material and its application in organic electroluminescent devices (OLEDs). Background Art

[0002] Since Tang and Van Slyke and other scientists first reported organic light-emitting diode (OLED) devices in 1987, OLED technology has made significant breakthroughs, especially in the wide application of display technology and solid-state lighting. OLED has gradually replaced traditional liquid crystal display (LCD) technology due to its self-luminous characteristics, wide viewing angle, ultra-thin and light weight, and fast response speed. Red OLED devices, as an important branch of OLED technology, have attracted great attention from researchers due to their potential applications in display, lighting, medical and security fields. As an important component of full-color display technology, red OLED devices play a key role in flat-panel displays, televisions and mobile devices. Compared with blue and green OLEDs, the luminous efficiency of red OLEDs was relatively low in the early development process. This is mainly due to the narrow band gap of red light-emitting materials, which leads to an increase in non-radiative transitions and affects the external quantum efficiency (EQE). In recent years, the efficiency and stability of red OLEDs have been significantly improved by introducing new luminescent materials and optimizing device structures (Adv. Mater. 2022, 34, 2201442).

[0003] In the selection of red light OLED materials, phosphorescent materials and thermally activated delayed fluorescence (TADF) materials are the current research focus. Phosphorescent materials can achieve an internal quantum efficiency close to 100% due to their ability to utilize triplet excitons, significantly improving the luminescence performance of the device. However, phosphorescent materials often need to rely on complexes containing precious metals such as iridium or platinum, which are not only costly but also scarce in resources. Therefore, in recent years, researchers have gradually turned to exploring pure organic TADF materials. TADF materials can convert triplet excitons into singlet excitons through the Reverse Intersystem Crossing (RISC) mechanism, thereby achieving 100% exciton utilization, with lower costs and better environmental friendliness. (ACSAppl.Mater.Interfaces 2020,12,27,30652–30658)

[0004] However, most current red light TADF materials still face the problem of low luminescence color purity. The reorganization energy of the luminescent material is high, and it is easy to produce a wide emission peak, which limits the color gamut and resolution of the device. This problem mainly stems from the intramolecular vibration relaxation and intermolecular rotational coupling, which makes the emission bandwidth of TADF materials usually wide, and the half-maximum width (FWHM) of the emission peak can reach 80 to 100nm, which is difficult to meet the requirements of high color gamut. Therefore, how to develop efficient and narrow-spectrum red light TADF materials is one of the important topics in the current OLED research field (J.Am.Chem.Soc.2024,146,47,32826–32836). In recent years, Hatakeyama et al. (Chem. Soc. Rev., 2024, 53, 1624-1692) proposed a new molecular design strategy, namely Multiple Resonance Thermally Activated Delayed Fluorescence (MR-TADF), by designing aromatic compounds containing boron and oxygen (or nitrogen) with a planar structure. This design method significantly suppresses the vibrational relaxation phenomenon of molecules by utilizing the multiple resonance effect between boron atoms and nitrogen atoms, and effectively reduces the reorganization energy (reorganization energy, λ) during the excited state transition process. In addition, the planar rigid structure of the MR-TADF molecule reduces the vibration and rotation of the molecule in the excited state, thereby reducing the half-width (FWHM) of the material's luminescence and achieving a narrow spectrum emission of less than 70nm. The advantage of this narrow spectrum is of great significance for improving the color purity and display performance of OLED devices.

[0005] The core of MR-TADF is to optimize the excited state energy level structure of the molecule by using the multiple resonance effect. In the traditional TADF molecular design, the energy difference between the triplet state and the singlet state (ΔE ST ) is a key factor affecting RISC efficiency. In order to improve the efficiency of TADF, molecular design is usually used to minimize ΔE ST value, triplet excitons can be effectively converted to singlet excitons through the RISC mechanism, thereby improving the luminescence efficiency. STThe strategy often leads to changes in the molecular structure, which in turn increases the vibrational relaxation phenomenon of the molecule, broadens the luminescence spectrum, and affects the color purity of the device. The MR-TADF molecule maintains the energy difference between the excited state and the ground state of the molecule in an ideal range through the multiple resonance effect, which can significantly suppress the effect of the vibration energy level and finally achieve narrow spectrum luminescence. The design of the multiple resonance effect of MR-TADF depends on a specific molecular structure. At present, most studies focus on aromatic compounds containing boron and nitrogen. This molecular design system is relatively single, resulting in limited development space for new materials. Especially in the red light band (Mater.Horiz., 2023, 10, 3712-3718), MR-TADF materials that can achieve efficient narrow spectrum emission are still scarce, which limits their practical application in these bands. The synthesis of MR-TADF molecules usually involves multiple complex reaction steps and requires precise molecular structure control, which not only increases the research and development cost of the material, but also increases the difficulty of synthesis, limiting the feasibility of large-scale production. In addition, the yield in the synthesis process is often low, further increasing the barriers to commercialization. It is urgent to develop new red light MR-TADF materials with simple structure and easy synthesis. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present invention designs a class of organic red light emitting materials with MR-TADF characteristics, and utilizes the synergistic effect of MR and TADF to achieve efficient narrow-band luminescence of MR-TADF red light emitting materials and their application in organic electroluminescent diodes.

[0007] The invention uses quinoline [3,2,1-de] acridine-5,9-dione as the central core and fused oxygen-bridged triphenylamine to construct a type of MR-TADF red light emitting material with a rigid large plane.

[0008] The present invention provides a type of MR-TADF red light emitting material with a narrow half-width having a structure shown in Formula 1:

[0009]

[0010] Wherein: the R units are independently selected from any one of the following formulae:

[0011]

[0012] The specific structures of the preferred MR-TADF red light emitting materials are shown below, and these compounds are only representative compounds:

[0013]

[0014] The R unit in the more preferred MR-TADF red light emitting material is tert-butyl, and the molecular structure is named LYZ.

[0015]

[0016] The preparation steps of MR-TADF red light emitting material LYZ are as follows:

[0017] Using 4-(tert-butyl)phenol as a raw material, 4-(tert-butyl)-2-iodo-1-methoxybenzene is obtained by iodination and methoxy protection of the hydroxyl group, and 4-bromo-2,6-difluoroaniline is subjected to Ullmann reaction, methoxy deprotection and nucleophilic substitution ring-closure reaction to obtain the tert-butyl nitrogen oxide core unit (D); using methyl 2-iodobenzoate and methyl 2-aminobenzoate as raw materials, 6,6'-azadiylbis(3-(tert-butyl)benzoic acid dimethyl ester unit (A) is obtained by Ullmann reaction and Friedel-Crafts alkylation reaction; D and A units are subjected to Ullmann reaction, ester hydrolysis reaction and Friedel-Crafts acylation ring-closure reaction to obtain the target product.

[0018] The present invention also provides the application of MR-TADF red light emitting material, which is used as a light emitting layer material for preparing red light OLEDs.

[0019] The structure of the MR-TADF red light organic electroluminescent device is: ITO / PEDOT:PSS(40nm) / PVK(5nm) / CBP:LYZ(1:1,40nm) / TmPyPB(40nm) / LiF(1.2nm) / Al(120nm). The hole transport layer is a polyvinyl carbazole (PVK) coating; the electron transport layer is TmPyPB; the light-emitting layer is a guest material (LYZ) and a host material blended coating; the host material is 4,4'-di(9-carbazole)biphenyl (CBP); and the cathode layer is composed of lithium fluoride and aluminum.

[0020] The MR-TADF red light emitting material LYZ was used to prepare the light emitting layer of red light OLEDs. The maximum emission peak of the obtained red light emitting device was located at 601nm, the half-peak width was 68nm, and the corresponding maximum external quantum efficiency (EQE) was 9.38%.

[0021] The quinoline acridine-5,9-dione MR-TADF red light luminescent material molecules provided by the present invention promote the minimization of bonding / anti-bonding of frontier molecular orbitals through the resonance effect generated by electron-deficient nitrogen / carbonyl and electron-rich oxygen / nitrogen. In addition, the rigid conjugated skeleton can suppress the structural relaxation of the molecular excited state and the vibration coupling between the excited state and the ground state, thereby obtaining a red light luminescent material with a narrow half-peak width (<70nm) and high luminescence efficiency; in order to weaken the face-to-face vibration of the molecule and effectively suppress the interaction between molecules, the introduction of tert-butyl groups on the periphery of the molecule can reduce the reorganization energy of the molecule; and the grafting of different substituent units can regulate the stacking of the molecule and its film-forming properties.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] (1) The molecular structure of the MR-TADF red light emitting material of the present invention breaks through the limitation of the MR-TADF red light emitting material being limited to a boron-carbon structure.

[0024] (2) The resonance effect between electron-deficient nitrogen / carbonyl and electron-rich oxygen / nitrogen minimizes the bonding / antibonding of the frontier molecular orbitals to reduce the vibrational relaxation of the fused ring structure, resulting in a narrow half-width and high luminescence efficiency.

[0025] (3) Compared with the reported MR-TADF red light emitting material molecules, the MR-TADF red light emitting material of the present invention has a larger coplane, which not only further suppresses the vibration relaxation of the molecules during the transition process, but also greatly suppresses the energy loss caused by the vibration and rotation of the molecular plane, further reducing the reorganization energy of the molecules during the transition from the excited state to the ground state, thereby obtaining a narrower emission spectrum.

[0026] (4) The introduction of tert-butyl, tert-butylphenyl, triarylamine, and carbazole groups on the periphery of the molecule can not only reduce the reorganization energy of the molecule, but also regulate the stacking of the molecule and its film-forming properties; it also reduces the structural deformation of the molecule in the excited state.

[0027] (5) The MR-TADF red light organic light-emitting material of the present invention can be used as a light-emitting layer material and applied to red light OLEDs devices to achieve efficient red light emission of OLEDs devices.

[0028] (6) This type of MR-TADF red light organic luminescent small molecule material has high thermal stability and excellent carrier transport performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The UV-visible light absorption spectrum and photoluminescence spectrum of the compound LYZ prepared in Example 1 of the present invention in toluene solution are shown.

[0030] Figure 2 This is the CV diagram of compound LYZ prepared in Example 1 of the present invention.

[0031] Figure 3 This is the TGA chart of compound LYZ prepared in Example 1 of the present invention.

[0032] Figure 4 Schematic diagram of the device structure of compound LYZ prepared in Example 1 of the present invention.

[0033] Figure 5 This is the EL spectrum of the compound LYZ prepared in Example 1 of the present invention under 10% doping.

[0034] Figure 6 This is the EQE spectrum of the compound LYZ prepared in Example 1 of the present invention under 10% doping.

[0035] Figure 7 This is the JVL diagram of the compound LYZ prepared in Example 1 of the present invention under 10% doping. DETAILED DESCRIPTION

[0036] The present invention is further described below by means of a specific example of a red light MR-TADF material LYZ based on quinolino[3,2,1-de]acridine-5,9-dione / dithione, but these specific embodiments do not limit the scope of protection of the present invention in any way.

[0037] Example 1

[0038] The synthesis scheme of the red light MR-TADF material LYZ based on quinolin[3,2,1-de]acridine-5,9-dione is as follows:

[0039]

[0040] Synthesis route of target compound LYZ

[0041] Synthesis of compound M1

[0042] In a 500mL single-necked flask, add 4-(tert-butyl)phenol (A, 100g, 665.7mmol, 1eq), N-iodosuccinimide (NIS, 149.8g, 665.8mmol, 1eq), p-toluenesulfonic acid (TsOH, 114.5g, 664.9mmol, 1eq), acetonitrile solution (CH3CN, 300.0mL), protect from light, and stir at room temperature for 6 hours. Stop the reaction, pour the reaction solution into 300mL ice water, add 300ml saturated sodium sulfite solution, and stir vigorously for 10 minutes. Separate the organic phase, remove the acetonitrile solution under reduced pressure, and vacuum dry at 60°C to obtain 173.9g of dark red viscous liquid, with a yield of 94.61%. 1H NMR (400MHz, CDCl3) δ7.63 (s, 1H), 7.26 (d, J = 8.4Hz, 1H), 6.91 (d, J = 8.5Hz, 1H), 5.30 (s, 1H), 1.27 (s, 9H).

[0043] Synthesis of compound M2

[0044] In a 500mL single-necked flask, add 4-(tert-butyl)-2-iodophenol (150g, 543.2mmol, 1.0eq), iodomethane (CH3I, 92.37g, 650.76mmol, 1.2eq), potassium carbonate (K2CO3, 112.6g, 814.8mmol, 1.5eq), N,N-dimethylformamide solution (DMF, 300.0mL), and stir at room temperature for 12 hours. Stop the reaction, pour the reaction solution into 800mL of water, extract with DCM three times (100mL*3), combine the organic phases, and wash with water 5 times (500mL*5). Separate the organic phase, dry with magnesium sulfate, filter to remove magnesium sulfate, remove DCM under reduced pressure, purify by rapid column chromatography with DCM as the developing solvent, and dry in vacuo at 60°C to obtain 128.7g of colorless viscous liquid with a yield of 82.54%. 1 H NMR (400MHz, CDCl3) δ7.77 (s, 1H), 7.32 (d, J = 8.6 Hz, 1H), 6.76 (d, J = 8.6 Hz, 1H), 3.86 (s, 3H), 1.28 (s, 9H).

[0045] Synthesis of Compound M3

[0046] Under nitrogen atmosphere, 4-(tert-butyl)-2-iodo-1-methoxybenzene (M2, 100 g, 344.67 mmol, 2.5 eq), 4-bromo-2,6-difluoroaniline (28.68 g, 137.87 mmol, 1 eq), activated copper powder (Cu, 35.05 g, 551.48 mmol, 4 eq), potassium carbonate (K2CO3, 95.26 g, 689.35 mmol, 5 eq), 18-crown-6 (18-Crown-6, 9.11 g, 34.47 mmol, 0.1 eq), o-dichlorobenzene (o-DCB, 500.0 mL) were added to a 1000 mL single-necked flask, and the temperature was raised to 180 ° C and stirred for 72 hours. The reaction was stopped, cooled to room temperature, filtered, and the filter cake was washed with 300 mL DCM, the filtrate was collected, and the organic solvent was removed by distillation under reduced pressure. The residue was poured into 300 mL of water, extracted with DCM three times (50 mL*3), the organic phases were combined, and washed with water 5 times (100 mL*5). The organic phase was separated, dried with magnesium sulfate, filtered to remove magnesium sulfate, and DCM was removed under reduced pressure. Column chromatography was performed with PE:DCM=2:1 as the developing solvent for separation and purification, and vacuum dried at 60°C to obtain 61.27 g of a white solid with a yield of 83.45%. 1 H NMR (400MHz, CDCl3) δ7.06 (dd, J = 8.5, 2.3Hz, 2H), 6.99 (d, J = 8.0Hz, 2H), 6.92 (d, J = 2.2Hz, 2H), 6.81 (d, J = 8.5Hz, 2H), 3.56 (s, 6H), 1.20 (s, 18H).

[0047] Synthesis of compound M4

[0048] Under nitrogen atmosphere, 4-bromo-N, N-bis(5-(tert-butyl)-2-methoxyphenyl)-2,6-difluoroaniline (M3, 5g, 93.90mmol, 1eq) and dry dichloromethane solution (DCM, 300.0mL) were added to a 500mL two-necked flask, cooled to 0°C, and boron tribromide (BBr3, 51.75g, 206.58mmol, 2.2eq) was slowly added, and the mixture was returned to room temperature and stirred for 12h. The reaction solution was poured into 500mL ice water to quench the reaction, extracted with DCM three times (50mL*3), the organic phases were combined, and washed with water three times (200mL*3). The organic phase was separated, dried with magnesium sulfate, filtered to remove magnesium sulfate, and DCM was removed under reduced pressure to obtain an off-white solid residue, which was directly used in the next step without further treatment. Under nitrogen atmosphere, a 500 mL two-necked flask was added with off-white solid residue, potassium carbonate (K2CO3, 38.93 g, 281.7 mmol, 3 eq) and N,N-dimethylformamide solution (DMF, 300.0 mL), heated to 120°C, and stirred for 12 h. The reaction was stopped, cooled to room temperature, and the reaction solution was poured into 800 mL of water to precipitate a large amount of white solid. The mixture was stirred vigorously for 30 min, filtered, and the filter cake was washed with distilled water (1500 mL). No further purification was required, and the filter cake was vacuum dried at 60°C to obtain 42.41 g of white solid, with a yield of 97.25%. 1 H NMR (400MHz, CDCl3) δ7.36 (s, 2H), 6.92 (dd, J = 8.5, 1.7Hz, 2H), 6.85-6.80 (m, 2H), 6.64 (s, 2H), 1.28 (s, 18H). MALDI-TOF MS(mass m / z):464.12[M]+.Calcd for C 26 H 26 BrNO2:464.40.

[0049] Synthesis of Compound M5

[0050] Under nitrogen atmosphere, methyl 2-iodobenzoate (28.83 g, 110 mmol, 1.1 eq), methyl 2-aminobenzoate (15.1 g, 100 mmol, 1 eq), activated copper powder (Cu, 12.7 g, 200 mmol, 2 eq), cuprous iodide (CuI, 3.8 g, 20 mmol, 0.2 eq), potassium carbonate (K2CO3, 27.6 g, 200 mmol, 2 eq), 18-crown-6 (18-Crown-6, 5.28 g, 20 mmol, 0.2 eq), and dry o-dichlorobenzene (o-DCB, 200.0 mL) were added to a 500 mL single-necked flask, and the mixture was heated to 180 ° C and stirred for 48 h. The reaction was stopped, cooled to room temperature, filtered, and the filter cake was washed with 300 mL DCM. The filtrate was collected and the organic solvent o-DCB was removed by distillation under reduced pressure. The residue was dissolved in a small amount of DCM and poured into 150 mL of petroleum ether (PE) to precipitate a white solid. The filter cake was filtered and washed with petroleum ether and dried in vacuo at 60° C. to obtain 27.92 g of a white solid with a yield of 97.96%. 1 HNMR (400MHz, CDCl3) δ11.07(s,1H),7.99(dd,J=8.0,1.6Hz,2H),7.55(d,J=8.0Hz,2H),7.37(t,J=7.8Hz,2H),6.90(t,J=7.6Hz,2H),3.95(s,6H).

[0051] Synthesis of compound M6

[0052] Add dimethyl 2,2'-azadiyldibenzoate (M5, 10g, 35mmol, 1eq) and tert-butyl chloride (C(CH3)3Cl, 60mL) to a 250mL single-necked flask, slowly add aluminum chloride (AlCl3, 11.67g, 87.5mmol, 2.5eq) in batches under an ice bath, raise the temperature to 70°C, pass condensed water, connect a drying tube, and stir the reaction for 12h. Stop the reaction, cool to room temperature, pour into 300mL of ice water, extract three times with DCM (50mL*3), combine the organic phases, and wash with water three times (50mL*3). Separate the organic phase, dry with magnesium sulfate, filter to remove the magnesium sulfate, and remove DCM and excess tert-butyl chloride under reduced pressure. The residue was dissolved in a small amount of DCM and poured into 150 mL of petroleum ether (PE) to precipitate a white solid. The filter cake was filtered and washed with petroleum ether and dried in vacuo at 60° C. to obtain 11.56 g of a white solid with a yield of 83.17%. 1H NMR (400MHz, CDCl3) δ 10.85 (s, 1H), 7.96 (s, 2H), 7.48 (d, J = 8.8Hz, 2H), 7.40 (dd, J = 8.8, 2.4Hz, 2H), 3.94 (s, 6H), 1.32 (s, 18H).

[0053] Synthesis of Compound M7

[0054] Under nitrogen atmosphere, a 250 mL single-necked flask was charged with 7-bromo-2,12-di-tert-butylbenzo[5,6][1,4]oxazine[2,3,4-kl]phenoxazine (M4, 2.1 g, 4.53 mmol, 1.2 eq), 6,6'-azadiylbis(3-(tert-butyl)benzoic acid dimethyl ester (M6, 1.5 g, 3.77 mmol, 1 eq), activated copper powder (Cu, 4.76 g, 75 mmol, 20 eq), cuprous iodide (CuI, 1.43 g, 7.5 mmol, 1 eq), potassium carbonate (K2CO3, 12.44 g, 90 mmol, 24 eq), 18-crown-6 (1. 98g, 7.5mmol, 1eq), dried o-dichlorobenzene (o-DCB, 60.0mL), heated to 180℃ and stirred for 48h. Stop the reaction, cool to room temperature, filter, wash the filter cake with 100mL DCM, collect the filtrate, and remove the organic solvent o-DCB by distillation under reduced pressure. Pour the residue into 200mL water, extract with DCM three times (50mL*3), combine the organic phases, and wash with water 3 times (50mL*3). Separate the organic phase, dry with magnesium sulfate, filter to remove magnesium sulfate, remove DCM under reduced pressure, and perform column chromatography separation and purification with PE:DCM=1:2 as the developing solvent, and dry in vacuo at 60℃ to obtain 1.99g of yellow solid, with a yield of 67.85%. 1 HNMR (400MHz, CDCl3) δ7.67-7.51(m,2H),7.49-7.20(m,4H),7.08-6.96(m,2H),6.92-6.53( m, 4H), 5.91 (d, J = 33.6Hz, 2H), 3.46 (d, J = 15.6Hz, 6H), 1.25 (d, J = 4.0Hz, 18H), 1.21 (s, 18H).

[0055] Synthesis of compound LYZ

[0056] A 500mL single-necked flask was added with 6,6'-((2,12-di-tert-butylbenzo[5,6][1,4]oxazin[2,3,4-kl]phenoxazine-7-yl)azadimethyl)bis(3-(tert-butyl)benzoate) (M7, 1.17g, 1.5mmol, 1eq), sodium hydroxide (NaOH, 12g, 300mmol, 200eq), tetrahydrofuran (THF, 80.0mL), ethanol (EtOH, 80.0mL), and distilled water (THF, 80.0mL), and the mixture was heated to 100°C and stirred under reflux for 4h. The reaction was stopped, THF and EtOH were removed by rotation, and the mixture was cooled to room temperature. The mixture was acidified with hydrochloric acid, and the pH was adjusted to 2-3. A yellow solid was precipitated, and the filter cake was filtered and washed with distilled water. The filter cake was dried under vacuum at 60°C to obtain 0.783g of a yellow solid with a yield of 69.42%. The mixture was used directly in the next step without purification. Under nitrogen atmosphere, add the yellow solid (0.783g, 1.04mmol, 1eq) from the previous step, oxalyl chloride (C2Cl2O2, 1.32g, 10.4mmol, 10eq), and dry dichloromethane (DCM, 15mL) from a 50mL single-necked flask, heat to 50°C, reflux, stir and react for 3h. Stop the reaction, remove C2Cl2O2 and DCM by vacuum distillation to obtain a gray solid, which is used directly in the next step without purification. Under nitrogen atmosphere, add the gray solid (0.780g, 1mmol, 1eq) from the previous step, aluminum chloride (AlCl3, 1.65g, 10mmol, 10eq), and dry dichloromethane (DCM, 15mL) from a 100mL single-necked flask, heat to 55°C, reflux, stir and react for 12h. Stop the reaction, and remove DCM by rotary evaporation. The residue was poured into 300 mL of water, extracted with DCM three times (20 mL*3), the organic phases were combined, and washed with water three times (30 mL*3). The organic phase was separated, dried with magnesium sulfate, filtered to remove magnesium sulfate, and DCM was removed under reduced pressure. Column chromatography was performed with PE:DCM=4:1 as the developing solvent for separation and purification, and vacuum dried at 60°C to obtain a red solid product LYZ, 0.263 g, with a yield of 24.35%. 1 H NMR (400MHz, CDCl3) δ8.37(s,2H),7.87(d,J=8.9Hz,2H),7.64(d,J=8.9Hz,2H),7.3 5(s,2H),7.12(d,J=8.5Hz,2H),7.00(d,J=8.5Hz,2H),1.42(s,18H),1.30(s,18H).

[0057] Example 2

[0058] UV absorption test of red light MR-TADF material LYZ based on quinoline [3,2,1-de] acridine-5,9-dione in toluene solution: Dissolve compound LYZ in toluene solution to prepare 10 -5 mol / solubility solution, test the UV-visible absorption spectrum of its toluene solution. Figure 1 It can be seen that the UV-visible absorption spectrum of compound LYZ in toluene has two absorption peaks: the absorption band around 300-400nm is attributed to π-π* transition, and the absorption band around 450-550nm is attributed to intramolecular charge transfer.

[0059] Example 3

[0060] Fluorescence spectrum test of toluene solution of quinoline [3,2,1-de] acridine-5,9-dione red light MR-TADF material LYZ: Photoluminescence performance test of compound LYZ in Example 1. Dissolve compound LYZ in toluene to prepare 10 -5 M solution, and tested the photoluminescence spectrum of the solution, such as Figure 1 As shown, under light excitation, all compounds are in the orange-red to red light region. Among them, the maximum emission peak of compound LYZ is 602nm, which meets the requirements of red light emission, and the half-peak width is 69nm, which has the characteristics of narrow half-peak width emission.

[0061] Example 4

[0062] CV test of red light MR-TADF material LYZ based on quinolin[3,2,1-de]acridine-5,9-dione: CV test of compound LYZ in Example 1. Figure 2 As shown, cyclic voltammetry (CV) was performed in anhydrous acetonitrile solution under nitrogen atmosphere using a CHI620 voltammetric analyzer at a scan rate of 50 mV / s. A platinum working electrode, a platinum wire counter electrode, and an Ag / AgCl electrode were used as the working electrode, counter electrode, and reference electrode, respectively. An acetonitrile solution of tetrabutylammonium hexafluorophosphate (Bu4NPF6, 0.1 M) was used as a reference for all measurements at a scan rate of 50 mV / s. Ferrocene / ferrocene cation (Fc / Fc + ) redox couple as reference. The measured oxidation potentials of LYZ were 0.73 eV, ferrocene / ferrocene cation (Fc / Fc + ) is 0.43 eV. The HOMO energy level of LYZ is calculated to be -5.10 eV, and the LUMO energy level can be calculated from the optical band gap.

[0063] Example 5

[0064] Thermal stability (TGA) test of red light MR-TADF material LYZ based on quinolin[3,2,1-de]acridine-5,9-dione

[0065] TGA test of compound LYZ in Example 1. The test was conducted from room temperature to 600°C at a heating rate of 20°C / min in a nitrogen atmosphere. The sample mass was controlled within 1g. The crucible was made of alumina (Al2O3) to ensure the stability and accuracy of the high temperature test and avoid sample oxidation, thus providing reliable data for subsequent analysis. Figure 3 As shown, the decomposition temperature (95% mass) of compound LYZ is 382° C., which has excellent thermal stability and meets the device processing performance.

[0066] Example 6

[0067] Device fabrication scheme and luminescence performance test of red MR-TADF material LYZ based on quinoline [3,2,1-de] acridine-5,9-dione

[0068] The structure of the red organic electroluminescent device is: ITO / PEDOT:PSS (40nm) / PVK (5nm) / CBP:LYZ (1:1, 40nm) / TmPyPB (40nm) / LiF (1.2nm) / Al (120nm). Figure 4 As shown. The hole transport layer is a polyvinyl carbazole (PVK) coating; the electron transport layer is 1,3,5-tri(p-pyridin-3-ylphenyl)benzene (TmPyPB); the light-emitting layer is a guest material (LYZ) and a host material blend coating; the host material is 4,4'-di(9-carbazole)biphenyl (CBP); and the cathode layer is composed of lithium fluoride and aluminum.

[0069] The device fabrication procedure is as follows: On the treated ITO glass, a 40nm poly(ethylenedioxythiophene) / poly(p-styrene sulfonic acid) (PEDOT-PSS) (Bayer Batron P4083) hole injection layer, a 5nm PVK hole transport layer and a 40nm light-emitting layer, a 40nm electron transport layer TmPyPB are spin-coated, and then 1.2nm lithium fluoride and 120nm aluminum (Al) layers are evaporated in sequence. The device has a light-emitting area of ​​0.15cm 2 .

[0070] The thickness of the hole injection layer, hole transport layer and light emitting layer was measured by a surface profiler (Tencor, ALFA-Step500). The thickness and deposition rate of the electron transport layer, hole injection layer and Al were measured by a thickness / speed meter (Sycon's STM-100 thickness / speed meter). The deposition rates of the electron transport layer, hole injection layer and Al were 0.05-0.1 nm / s and 1-2 nm / s, respectively. All operations were performed in a nitrogen glove box.

[0071] The electroluminescence spectrum (EL) was measured using an Instaspec4CCD grating spectrometer from Oriel; the luminous efficiency was measured using a standard silicon photodiode; the electroluminescence efficiency was measured using an S80 integrator (USLabshere) in conjunction with a UDT3 digital photometer; the laser light source was a He-Cd laser with 325 and 442nm spectral lines (USDmni Chrone); the current-voltage (IV) curve, the luminescence intensity-voltage (LV) curve and the external quantum efficiency were measured using a Keithley source meter.

[0072] The electroluminescence spectra and EQE curves of the light-emitting devices based on LYZ materials are shown in Figure 5-6 As shown. The LYZ-based doped device shows a red light emission spectrum, showing strong luminescence in the range of 550nm to 750nm. When the material LYZ is used to prepare red light organic light-emitting diode devices, the LYZ-based (10% doped) device has a luminescent wavelength of 601nm (EQE of 9.38%) and a half-peak width of 68nm, achieving narrow-band red light emission. Figure 7 As shown, the current density, voltage-luminance (JVL) characteristic curve of the device has a medium relative current density and a turn-on voltage of (8.1V).

[0073] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.

Claims

1. A type of quinoline acridine-5,9-dione MR-TADF red light emitting material, characterized in that: The molecular structure of the luminescent material is shown in Formula 1: Wherein: the R units are independently selected from any one of the following formulae:

2. The quinolineacridine-5,9-dione MR-TADF red light emitting material according to claim 1, characterized in that: The R unit is tert-butyl.

3. The method for preparing the quinolineacridine-5,9-dione MR-TADF red light emitting material according to claim 2, characterized in that: The method comprises the following steps: using 4-(tert-butyl)phenol as a raw material, obtaining 4-(tert-butyl)-2-iodo-1-methoxybenzene through iodination and methoxy protection of hydroxyl group, and obtaining tert-butyl nitrogen oxide core unit through Ullmann reaction, methoxy deprotection and nucleophilic substitution ring-closing reaction of 4-bromo-2,6-difluoroaniline; using methyl 2-iodobenzoate and methyl 2-aminobenzoate as raw materials, obtaining 6,6'-azadiylbis(3-(tert-butyl)benzoic acid dimethyl ester unit through Ullmann reaction and Friedel-Crafts alkylation reaction; obtaining the target product through Ullmann reaction, ester hydrolysis reaction and Friedel-Crafts acylation ring-closing reaction of the tert-butyl nitrogen oxide core unit and the 6,6'-azadiylbis(3-(tert-butyl)benzoic acid dimethyl ester unit.

4. Use of the quinolineacridine-5,9-dione MR-TADF red light emitting material according to claim 1 as a light emitting material in preparing a red light organic electroluminescent device.

5. The use according to claim 4, characterized in that: The quinoline acridine-5,9-dione MR-TADF red light emitting material is used as a guest light emitting material.

6. The use according to claim 4, characterized in that: The structure of the red light organic electroluminescent device is: ITO / PEDOT:PSS / PVK / CBP:LYZ / TmPyPB / LiF / Al; wherein the LYZ is the quinoline acridine-5,9-dione MR-TADF red light luminescent material according to claim 2.

Citation Information

Patent Citations

  • Thermally activated delayed fluorescent material constructed based on nitrogen-containing heteroaromatic ring derivative and carbonyl and application of thermally activated delayed fluorescent material

    CN113980019A

  • Near-infrared thermal activation delayed fluorescence luminescent material based on dicyanophenene and application of near-infrared thermal activation delayed fluorescence luminescent material

    CN115490631A

  • Narrow-bandwidth luminescent material

    JP2022132140A

  • Mr-HLCT near-ultraviolet luminescent material and use thereof in oleds

    WO2023165325A1